PFM.69 Customised vs uncustomised ultrasound charts in the assessment of perinatal mortality risk in the South Asian maternity population. (9th June 2014) - Giddings, S; Clifford, S; Madurasinghe, V; Gardosi, J
Abstract : Background: Small for gestational age (SGA) birthweight has an increased association with perinatal mortality when defined by a customised instead of a population based standard. 1 We wanted to examine whether this applies also to ultrasound estimated fetal weight (EFW) in a South Asian cohort. Method: The data were extracted from an NHS regional database of singleton, normally formed pregnancies collected between 2009–2012. Of a total of 141, 731 pregnancies, 18, 400 (13.0%) were of South Asian mothers (Indian, Pakistani or Bangladeshi). In pregnancies with more than one growth scan, the last scan was used for analysis. SGA (<10 th centile) EFW was assessed by the conventional Hadlock chart or by GROW (gestation related optimal weight), customised for maternal height, weight, parity and ethnic origin. 2 Results: 10, 405 (56.5%) of the pregnancies had one or more growth scans. The EFW was SGA according to Hadlock in 1554 (14.9%) of cases, and according to GROW in 706 (6.8%). The relative risk for perinatal death was 3.7 (CI 2.1–6.4) for SGA-Hadlock, and 5.7 (CI 3.2–10.4) for SGA-GROW. 16 EFWs were designated SGA by GROW only, but 864 of the 1554 EFWs (55.6%) were SGA by Hadlock only. This group had the same risk for perinatal mortality as non-SGA fetuses (RR 1.2; CI 0.5–3.0). Conclusion: Use of a population based fetal weight standard more than doubles the number of growth scans of South Asian mothers being designated SGA, without any increase in perinatal mortality risk, and is likely to create unnecessary anxiety and interventions in otherwise normal pregnancies. References: BJOG 2009;116(10):1356–63 www.gestation.net